University knowledge spillover from an open innovation technology transfer context. Issue 1 (2nd January 2021) - Davies, Gareth Huw; Flanagan, Joe; Bolton, David; Roderick, Sian; Joyce, Naomi
ABSTRACT: University research output is a recognised source of new knowledge in spillover theory, targeted by governments and other stakeholders to support regional economic development. This paper reflects upon the 'AgorIP' Technology Transfer initiative, examining how a University can support knowledge spillover within an innovation ecosystem. The paper aims to contribute to understanding of how local characteristics moderate knowledge spillover-supported new enterprise. AgorIP supports entrepreneurship, extending academic traditional technology transfer to also harness health system research output. This paper extends contextual spillover research through university and regional policy, by examining AgorIP's portfolio of completed projects and current partners. The findings present spatial concentration within the local region, with focus on targeted smart specialisations, including Life Sciences & Health. The post-industrial peripheral nature of the region makes AgorIP's context of potential interest to others looking to harness the potential of university and other public research organisations in developing knowledge-based enterprise.